Rhetoric in Song Lyrics Malam Terakhir and Satukan Hati Kami as Contribution for Character Building Through Literature Education - Sugeng Purwanto; Endang Yuliani Rahayu (AKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
The current study aims to analyze the rhetoric employed in two song lyrics, namely Rhoma Irama’s Malam Terakhir and Pance Pondaag’s Satukan Hati Kami to identify the similarities and differences in creating the values of religiousness and romantisism in order to contribute to Indonesian Literature Education in relation to youth’s character building. With the use of genre analytical framework under discourse analysis, the two song lyrics were analyzed to identify (1) communicative purposes, (2) generik structure and (3) linguistis features. Meanwhile, to investigate the value of religiousness and romantisism, a survey was administered to 20 students of Faculty of Language and Cultural Studies, Stikubank University only to find out that the two song lyrics created different discourses with different proportion of religiousness and romantisism. The findings yielded conclusion and recommendations to further expand the scope of literature teaching, especially with respect to the youth’s character building.